The "Negative" Assimilation of Immigrants: A Special Case - Chiswick, B.; Miller, Paul (Cornell University. New York State School of Industrial and Labor Relations, 2011)
The authors address whether “negative” assimilation among immigrants living in the United States occurs if skills are highly transferable internationally. They outline the conditions for negative assimilation in the context of the traditional immigration assimilation model, in which negative assimilation arises not from a deterioration of skills but from a decline in the wages afforded by skills coincident with the duration of residence. The authors use U.S. Census data from 1980, 1990, and 2000 to test the hypothesis on immigrants to the United States from English-speaking developed countries. They present comparisons with native-born workers to determine whether the findings are sensitive to immigrant cohort quality effects and find that even after controlling for these effects, negative assimilation still occurs for immigrants in the sample. They also find that negative assimilation occurs for immigrants from English-speaking developed countries living in Australia and for immigrants from Nordic countries living in Sweden.